PARENTAL DIVORCE'S EFFECTS ON STUDENT CHARACTER AT ISLAMIC ELEMENTARY SCHOOL - Ilma Nabila; Nur Khosiah; Yulina Fadilah (El Midad, 2024)
This study examines parental divorce's impact on elementary school children at MI Hidayatul Islam Clarak. The research employs a qualitative method with a case study approach. Data collection techniques used in this study include interviews and observations. The subjects of this research are 10 students from MI Hidayatul Islam Clarak, one teacher, and two student guardians. The student subjects were selected from families who have experienced divorce. The age range of the research subjects is between 7 and 12 years old, corresponding to elementary school age. The results indicate that following a divorce, most children tend to live with their mothers, while only a few live with their fathers. Additionally, it is not uncommon for children after a divorce to be taken in by one of their grandmothers and enrolled in an elementary school, such as MI Hidayatul Islam, where the research was conducted. Research findings indicate that the impact of parental divorce on students' character can be observed primarily in psychological dimensions. Emotionally, children often experience feelings of loss, confusion, and even anxiety due to changes in family support, especially when they live only with their mother or other relatives, such as a grandmother. This limited parental presence may lead to a perceived lack of attention or support from their father, affecting their emotional stability. Psychologically, children may face identity crises and become more vulnerable to issues like prolonged insecurity or depression, which can have long-term effects on their character development and behavior.